ANALISIS USAHATANI KENTANG DI KAMPUNG DEMUNTI DISTRIK HINGK KABUPATEN PEGUNUNGAN ARFAK - Ismail; Simanungkalit, Saut; Palit, Maria (Sosio Agri Papua, 2023)
The aims of this study were (1) to determine the cost, revenue and income of a potato farming in Demunti Village, Hingk District, Arfak Mountains District. (2) Analyzing the efficiency of potato farming in Demunti Village, Hingk District, Arfak Mountains District. The data used in this study were primary data obtained through direct interview techniques with farmers based on a list of questions while secondary data were obtained from other relevant agencies such as the Demunti Village office. The data obtained from this study were analyzed descriptively, and the data collected was presented in tabular form and continued with the calculation of receipts, costs, income, R/C analysis and break-even analysis (BEP). The results of this study indicate that the average income of potato farming in Demunti Village is IDR 3,222,333.33 and the costs incurred in the production process average IDR 1,048,528.00. So that the average income of farmers in one planting season is IDR 2,173,805.33. The income of potato farming in Demunti Village, Hingk District, Arfak Mountains Regency, seen from the results of the analysis, the Return Cost Rtio (R/C) is greater than 1, namely 3.07. This indicates that the income received by farmers in one planting season is profitable and break events. point (BEP) was achieved at a production level of 56.67 kg and at a price level of IDR 4,966.9 /kg.